Does the Modern General Theory of State and Law Remain a Fundamental, Methodological Juridical Science? - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics University, 2021)
This scientific article is devoted to the general theory of state and law as a fundamental, methodological legal science at all stages of its development. The article substantiates the position according to which its belittling both at the theoretical and at the practical levels is unreasonable.